Effectiveness of Eggshell Waste as Toothpaste Abrasive Agent with Optimal Toothbrushing Parameter - Shakilla Nur Asimah Mat Hussin,; Shahmir Hayyan,; Mohd Zulkarnain Mohd Zakri,; Ola Barakat Al-Batayneh,; Sarliza Yasmin Sanusi, (International Journal of Integrated Engineering, 2026)
This study explores the potential of eggshell waste as an alternative material for abrasive agent in toothpaste formulations while addressing the limited understanding of its abrasive characteristics during toothbrushing process. Experimental investigations were conducted using a Reciprocating Toothbrushing Test Rig on acrylic surfaces, selected for their high scratch resistance, clarity, and compositional similarity to artificial teeth which provides a standardized and controlled testing environment for preliminary abrasive characterization studies. Abrasive performance was evaluated based on scratch factor, drag factor, scratch patterns, and scratch depth. The results highlighted that effective toothbrushing can be achieved with parameters of 1 N brushing load, 100 rpm brushing speed (92 mm/s), and a minimum of 20 brushing cycles. Validation test confirmed that these parameters are able to remove 0.1 µm of artificial stain without damaging the surface. This research provides foundational tribological data for eggshell waste utilization and establishes preliminary toothbrushing parameters, while acknowledging the need for future clinical validation on natural dental tissues. This research highlights the feasibility of utilizing eggshell waste as an eco-friendly abrasive agent and establishes effective toothbrushing parameters that enhance oral hygiene while promoting sustainability.